Developing Students Soft Skills Using the Cooperative Learning Model at SMP Negeri 4 Nirunmas - Melmambessy, Leonarda; Leuwol, Ferdinand Salomo; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This research aims to uncover the development of students' soft skills and the influencing factors within the Cooperative Learning model implementation context. The study utilizes a field research approach and adopts a descriptive qualitative method. The research is conducted at SMP Negeri 4 Nirunmas, and data is gathered from primary and secondary sources through observation, in-depth interviews, and documentation. Research variables encompass leadership, teamwork, creativity, and responsibility. The findings indicate that developing students' soft skills through the Cooperative Learning model requires active involvement from teachers. Firstly, teachers must establish a character model emphasizing honesty, discipline, responsibility, and teamwork. Creating a supportive learning environment also encourages self-confidence and group collaboration. Factors influencing the development of soft skills can be categorized into supportive and inhibitory factors. Supportive factors include student motivation, intelligence, parental involvement, and the surrounding environment. Meanwhile, inhibitory factors comprise physical maturity or growth, peer interaction, and exposure to potentially harmful media influences.